An Embedded System for Determining Free Glycerol Level in Biodiesel - Eggly, Gabriel M.; Diniz, Paulo H. G. D.; Santos, Rodrigo; Pistonesi, Marcelo F.; Aráujo, Mário C. U.; Band, Beatriz Fernández (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Industrial products require strict quality controls and many times these are related to the chemical composition. Traditional reference methods for doing these are expensive and require sophisticated equipment. Flow-Batch (FB) and Flow Injection Analysis (FIA) methodologies have been contributing to perform quality control in industrial processes. Biodiesel, fuel produced from vegetable oil or animal fats, should be tested to guarantee that the free glycerol level present in it is not beyond the standard. In this paper, an embedded system that combines FB and FIA methodologies is proposed for the pretreatment of the sample and the determination of glycerol level in biodiesel samples. The system proposed cost less than two hundred dollars, is portable and provides the necessary precision. The system was tested with samples obtained from Petrobras Oil company in Bahia Blanca (Argentina) without previous treatment and was validated using a recovery analysis. Results obtained are between 98% and 102%.